Simbol Mantaa Duku' - Kinaa Editor; Kristanto Kristanto (KINAA: Jurnal Teologi, 2016)
This article was retracted by Junal Kinaa - Theology Faculty of the Christian University of Indonesia Toraja. The publisher found that the main author Kristanto violated copyright prudence and was suspected of violating works and copying works from other parties. The editor of the Kinaa Journal takes the value of intellectual property seriously so that as a consequence of this violation the article above is declared withdrawn.